2019
DOI: 10.1016/j.jvir.2018.12.654
|View full text |Cite
|
Sign up to set email alerts
|

Abstract No. 573 Radial versus femoral access: is there a preference among nursing care providers?

Abstract: data from 1086 procedure reports from the six months prior to implementation and 1270 procedure reports from the six months after implementation were reviewed to assess changes in code usage. Results: Structured reporting increased the number of CPT codes per procedure (2.93 vs 3.90, p<0.01). Structured reporting increased the use of codes for fluoroscopic guidance for central venous catheter placement, ultrasound guidance for vascular access, time-based moderate sedation, and 3D rendering with interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…15 It has been demonstrated that the cost of procedures and the complication rate are higher, and the length of hospital stay is longer in patients treated with transfemoral vascular access. 7,11,12,16 After angiography and interventional coronary applications, there are studies involving pain assessment for nursing care. Although it has been reported in the studies that interventions with radial access increase patient comfort, there is a very limited number of studies in which comfort level is evaluated using a comfort scale.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been demonstrated that the cost of procedures and the complication rate are higher, and the length of hospital stay is longer in patients treated with transfemoral vascular access. 7,11,12,16 After angiography and interventional coronary applications, there are studies involving pain assessment for nursing care. Although it has been reported in the studies that interventions with radial access increase patient comfort, there is a very limited number of studies in which comfort level is evaluated using a comfort scale.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, treatment with transfemoral vascular access reported to bring higher cost of procedures, higher complication rates and longer time spent at hospital. 7,11,12,16 There are studies involving pain assessment after coronary interventions for nursing care. Although some studies have reported that interventions with radial access increase patient comfort, there are very few studies in which comfort level is evaluated using a comfort scale.…”
mentioning
confidence: 99%